The Priority of the Church’s Ministry during a Pandemic - Ardi Raharjo Sastrohartoyo; Rubin Adi Abraham; Jantje Haans; Tjahyadi Chandra (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2021)
The global COVID-19 pandemic has caused churches to change their worship patterns from meeting at church buildings to virtual worship at home to prevent transmission of the virus and comply with the health protocols set by the local governments. This study aims to determine the priority of the pastoral ministry during the COVID-19 pandemic and explore new strategies to be adopted analyze and examine the functions of the church, especially with regards to how the church responds previously during the pandemic and determines the priority of the church's ministry to continue to do the Great Commission and the Great Commandment amid the COVID-19 pandemic. This study uses the descriptive qualitative method by researching relevant literature using Biblical perspective. Based on this study, we   recommend that churches to embrace digital online technology for digital evangelism to effectively reach, connect and engage with many people who are more connecting to social media platforms. Online church is an effective tool for evangelism and missiology to extend the reach and enable the spread of the Gospel worldwide in the digital era. ABSTRAK: Pandemi global COVID-19 telah menyebabkan gereja-gereja untuk mengubah pola ibadahnya dari yang dilakukan di gedung gereja kepada pola ibadah virtual di rumah, sebagai upaya untuk mencegah transmisi virus dan mengikuti protokol-protokol kesehatan yang telah ditetapkan oleh pemerintah setempat.  Penelitian ini bertujuan untuk menganalisa dan menggali apa yang menjadi fungsi dari gereja, khususnya berkaitan dengan pertanyaan apa yang menjadi sikap gereja sebelumnya ketika diperhadapkan dengan pandemi dan untuk mengetahui akan apa yang menjadi prioritas pelayanan gereja untuk tetap dapat melakukan apa yang menjadi Perintah Utama dan Amanat Agung di masa COVID-19 pandemi. Metode yang digunakan bersifat kualitatif deskriptif melalui penelitian terhadap berbagai literatur yang relevan dengan menggunakan perspektif Alkitab. Berdasarkan penelitian ini, kami merekomendasikan gereja-gereja untuk memanfaatkan teknologi digital untuk dapat menjangkau, terhubung dan terlibat secara efektif dengan banyak orang yang sekarang menggunakan platform media sosial. Gereja online adalah alat yang efektif untuk melakukan pekabaran Injil dan misiologi untuk memperluas jangkauan penyebaran Injil ke seluruh dunia di era digital.